A novel nucleotide oligomerisation domain 2 mutation in a family with Blau syndrome: Phenotype and function. Issue 7 (October 2017) - Ong, Lawrence TC; Nachbur, Ueli; Rowczenio, Dorota; Ziegler, John B; Fischer, Eddy; Lin, Ming Wei
Mutations in the nucleotide binding domain of the PRR, NOD2, are associated with the autoinflammatory diseases Blau syndrome and early-onset sarcoidosis. Current theories suggest that constitutive activation of the NOD2 pathway may be responsible for pathogenesis of these diseases. Here, we report the phenotype of a kindred with Blau syndrome caused by a novel NOD2 mutation (p.E383D). Signaling protein and cytokine expression were examined, and the results of these experiments challenge current theories of constitutive NOD2 activation in the pathophysiology of Blau syndrome.